A review of the pre-chamber ignition system applied on future low-carbon spark ignition engines. (February 2022) - Zhu, Sipeng; Akehurst, Sam; Lewis, Andrew; Yuan, Hao
Abstract: Legislations for greenhouse gas and pollutant emissions from light-duty vehicles are pushing the spark ignition engine to be cleaner and more efficient. As one of the promising solutions, enhancing the ignition energy shows great potential in simultaneously mitigating combustion knock and enabling lean-burn operation. Featured with distributed ignition sites, pre-chamber ignition systems with large or small pre-chamber volumes, auxiliary or no auxiliary fueling, and large or small orifices have gained a surge of interest in decreasing the fuel consumption and pollutant emissions. This paper aims at presenting a comprehensive review of recent progress and development trends of pre-chamber ignition systems adopted on future low-carbon and low-emission spark ignition engines. First, mechanisms behind this technology are discussed from the perspectives of the pre-chamber scavenging and combustion, jet ejection, main chamber combustion, and emission formations. Second, the design criteria of pre-chamber geometries are presented in detail, followed by a discussion on the fuel and air management for the main chamber. Next, recent numerical and experimental studies on the pre-chamber ignition system and its applications in conjunction with other complementary technologies are summarized. Finally, critical issues for commercialization and future research directions are discussed. Highlights: The turbulent jet ignition applied on future gasoline engines was fully reviewed. Mechanisms of scavenging and combustion in the pre- and main chambers were discussed. Design criteria of pre-chamber geometries were presented in detail. Recent numerical and experimental studies on the turbulent jet ignition were compared. Critical issues in commercialization were summarized.